Ultrashort pulse capability at the L2I high intensity laser facility. (26th January 2017) - Figueira, Gonçalo; Alves, Joana; Dias, João M.; Fajardo, Marta; Gomes, Nuno; Hariton, Victor; Imran, Tayyab; João, Celso P.; Koliyadu, Jayanath; Künzel, Swen; Lopes, Nelson C.; Pires, Hugo; et al.
Abstract : The Laboratory for Intense Lasers (L2I) is a research centre in optics and lasers dedicated to experimental research in high intensity laser science and technology and laser plasma interaction. Currently the laboratory is undergoing an upgrade with the goal of increasing the versatility of the laser systems available to the users, as well as increasing the pulse repetition rate. In this paper we review the current status of the laser research and development programme of this facility, namely the upgraded capability and the recent progress towards the installation of an ultrashort, diode-pumped OPCPA laser system.